Effects of Direct Double Auger Decay on the Population Dynamics of Neon Irradiated by Ultraintense x‐ray Pulses. Issue 2 (4th December 2014) - Gao, C.; Zeng, J.; Yuan, J.
Abstract: The population and charge state distribution of neon interacting with ultraintense x‐ray pulses are investigated by solving a time‐dependent rate equation in the detailed level‐accounting (DLA) approximation. Due to the detailed description of neon atom and ions, our DLA result improves the agreement between predictions and experimental measurements for odd neon charge states. In the framework of the DLA formalism, we further studied the effects of direct double Auger decay (DDAD) on charge state distribution. After the 1 s photoionization of neon atom, the DDAD processes give accessible decay channels from the K‐shell hole state of Ne + to levels of Ne 3+, resulting in an increase of the population fraction of Ne 3+ and a decrease of that of Ne 2+ . Compared with the results without considering the DDAD effects, better agreement is obtained between theory and experiment. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)